(3Yde GLJeGY GdefXeGJ (B: s (3GdSfI Chdi LPY eTJQc (B/ s - (3geGd, YHO GdeGdcs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eONd JGQjNj dJJHY eQGMd fTCI hOhQ Yde GLJeGY GdefXeGJ,jNU GdOQGSI GdShSjhdhLjI ddefXeI Ydi VhA Yde GLJeGY GdefXeGJ,Cge GdeQJcRGJ hGdebGQHGJ GdfXQjI GdJfXjejI GdJj JKjQ SDGd GdCOGAGdhXjaj,jgJe HJMdjd fSb GdKbGaI GdJfXjejI hGdaYGdjI GdJfXjejI, jfGbT hjMdd fXQjkG GdSdhc GdJfXjej aj EWGQ ShSjhdhLjG GdYed(B. s
(3GdeQGLY U(B.115s
Keywords: (3GdGLJeGY GdJfXjej(B-(3Ydes